Éléments sur l’apport de la doctrine américaine du public trust à la représentation de l’environnement devant le juge - Emilie Cornu-Thenard (VertigO)
The U.S. Public Trust Doctrine is an old tool undergoing important developments in the U.S. ( as illustrated by the Robinson Township case in Pennsylvania) and elsewhere. It offers interesting areas of reflection regarding environmental protection by and in the courts. This doctrine can be used to protect certain natural resources by imposing on public authorities to manage them for the use and interest of the public, including future generations. It thus implements notions of sustainable development and intergenerational equity, crucial to an effective environmental protection. This article describes briefly the origins of the doctrine, its parallels and differences with financial trusts, its current expansion and the limits of its scope, regarding the protected resources and the quality of the protection afforded via the obligations imposed on trustees. Finally, it examines the role of the judge, reflecting on the importance and effectiveness, real and potential, of this doctrine along with the obstacles faced by an effective representation and protection of the environment.